Born of ice - Kenyon, Sherrilyn, 1965- (Kenyon, Sherrilyn, 1965- League, 2009)
Devyn Kell, a Runner who makes sure planets get the weapons, medicine, and supplies they need to survive, finds himself in big trouble when he hires Alix Garran, who is trying hard to escape her dark past, as his systems engineer.